POTENSI ANTIMIKROBA EKSTRAK DAUN JAMBLANG (Syzygium cumini L.) DARI KAWASAN GEOTHERMAL IE SEUM ACEH BESAR - Munira Munira; Noni Zakiah; Rini Handayani; Muhammad Nasir (Jurnal Insan Farmasi Indonesia, 2022)
Jamblang leaf (Syzygium cumini L.) contains several antimicrobial compounds. The content of chemical compounds in a plant is influenced by environmental factors. The Geothermal area of Ie Seum Aceh Besar has a different temperature and pH of the soil. This research was conducted to determine the antimicrobial activity of jamblang leaf ethanol extract which grew inside and outside the geothermal area. This research is experimental laboratories using a complete randomized design (RAL). The study consisted of 3 treatments, namely distilled water, jamblang leaf extract which grew in the Geothermal area of Ie Seum (EDJDKG) and jamblang leaf extract that grew outside the Geothermal area of Ie Seum (EDJLKG) and each 5 replications. The results showed that jamblang leaf ethanol extract that grew inside and outside the geothermal area of Ie Seum was very influential (p = 0,000) in inhibiting the growth of Staphylococcus aureus, Escherichia coli and Candida albican. Duncan's further test results showed that the largest average inhibitory diameter was produced by EDJDKG (19.20 mm) and was not significantly different from EDJLKG (18.00 mm) in inhibiting the growth of S. aureus. As for E. coli EDJDKG of 20.70 mm and significantly different from EDJLKG (18.70 mm).